A Manager's Guide to Computer Timesharing (Book). - Dominak, Geraldine F.; St.Amand, Gerald (The Accounting Review, 1976)
Abstract Reviews the book "A Manager's Guide to Computer Timesharing," by Timothy P. Haidinger and Dana R. Richardson.